1980
DOI: 10.1083/jcb.86.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Localization of myosin, actin, and tropomyosin in rat intestinal epithelium: immunohistochemical studies at the light and electron microscope levels.

Abstract: Myosin, tropomyosin, and actin were localized in the epithelial cells of rat intestine by means of specific antibodies to chicken gizzard smooth muscle myosin, tropomyosin, and actin by immunohistochemical studies at both the light and electron microscope levels (unlabeled antibody enzyme technique) . The pattern of antibody staining was the following : (a) Anti-actin was associated with the microfilament bundles of the microvilli in their entire length, as well as with the microfilament network in the termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
68
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(75 citation statements)
references
References 29 publications
(56 reference statements)
6
68
1
Order By: Relevance
“…The rationale for these experiments was that tropomyosin is present on the actin filaments of the microvillus core rootlets (33,20) to which TW 260/ 240 molecules are presumably bound. Results of these experiments (Fig.…”
Section: Effects Of Salt and Temperature On The Organization Of The Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for these experiments was that tropomyosin is present on the actin filaments of the microvillus core rootlets (33,20) to which TW 260/ 240 molecules are presumably bound. Results of these experiments (Fig.…”
Section: Effects Of Salt and Temperature On The Organization Of The Tmentioning
confidence: 99%
“…Electron microscopy-immunolocalization studies using antibodies to either TW 260/240 (29) or brain fodrin (30) indicate that TW 260/240 (or its equivalent in mammalian brush borders) comprises at least one type of "interdigitating" filaments that cross-link core rootlets. A second class of cross-linking filaments that appear to be greater in diameter than the TW 260/240 filaments when visualized by the quick-freeze, deep-etch rotary replication (QFDERR)' technique (27) may be comprised ofbrush border myosin that, like TW 260/240, is localized exclusively in the terminal web (31)(32)(33)(34). The studies of Hirokawa et al .…”
mentioning
confidence: 99%
“…Light and EM immunocytochemical studies to date (2,7,9,18) have shown that the apices of intestinal cells contain the essential contractile proteins, including actin, myosin, tropomyosin, and a-actinin . EM has not revealed how all these proteins could fit together to provide rigid support and flexible contractility in an appropriate manner .…”
Section: The Cytoskeleton Of Intestinal Cellsmentioning
confidence: 99%
“…A large number of biochemical and immunocytochemical studies have focused on this region of the intestinal cell . These studies have defined the proteins that are present in the terminal web, but they have THE JOURNAL OF CELL BIOLOGY " VOLUME 91 NOVEMBER 1981 399-409 © The Rockefeller University Press -0021-9525/81/11/399/11 $1 .00not been able to demonstrate exactly how these proteins are put together (2,3,4,(6)(7)(8)(9)18) . The micrographs presented here display certain advantages over traditional transmission electron micrographs of plastic-embedded and sectioned material, and thus help to reveal how the terminal web is organized.…”
mentioning
confidence: 99%
See 1 more Smart Citation